THE EFFECT OF ACIDIC AND ALKALINE CONDITIONS ON FREE FATTY ACID CONTENT DURING THE TRANSESTERIFICATION OF WASTE COOKING OIL - Rismul Trianto Salawali; Resti Ayu Ningrum; Rika Silvany; Putri Rizky (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2026)
Waste cooking oil is a waste material with significant potential for utilization as a biodiesel feedstock; however, its high free fatty acid (FFA) content can reduce the efficiency of the transesterification process. This study aimed to investigate the effect of acidic and alkaline conditions on the presence of free fatty acids during the transesterification of waste cooking oil using sodium hydroxide (NaOH) and potassium hydroxide (KOH) catalysts. Prior to the transesterification process, the waste cooking oil was filtered and heated at 60°C for 30 minutes to reduce its moisture content. Transesterification was carried out using methanol at a methanol-to-oil molar ratio of 6:1 and a catalyst concentration of approximately 0.25% of the oil weight. The reaction pH was varied at 6, 7, 8, 9, and 10, while the reaction temperature was maintained at 60°C for 1 hour. FFA content was analyzed before and after transesterification using an acid-base titration method with 0.1 N NaOH solution. The results showed that the initial FFA content of the waste cooking oil was 5.20%. The use of the NaOH catalyst resulted in final FFA contents of 3.00%, 2.55%, 1.90%, 1.75%, and 2.20% at pH 6, 7, 8, 9, and 10, respectively, corresponding to FFA reductions of 42.3%, 51.0%, 63.5%, 66.3%, and 57.7%. Meanwhile, the KOH catalyst produced final FFA contents of 2.80%, 2.35%, 1.70%, 1.60%, and 2.05%, with FFA reductions of 46.2%, 54.8%, 67.3%, 69.2%, and 60.6%, respectively. The reduction in FFA content increased with increasing pH and reached its optimum condition at pH 9 for both catalysts. At pH 10, a decrease in FFA reduction efficiency was observed, which was likely attributed to the occurrence of side reactions such as saponification. Overall, the KOH catalyst demonstrated superior performance compared to NaOH in reducing FFA content under all tested pH conditions. These findings indicate that mildly alkaline to moderately alkaline conditions, particularly at pH 9, represent the optimum conditions for reducing FFA content during the transesterification of waste cooking oil.